THE EFFECTIVENESS OF NATURAL PLANT GROWTH REGULATORS (PGRS) FROM BEAN SPROUTS EXTRACT AND NPK 15-15-6-4 ON THE GROWTH OF OIL PALM SEEDLINGS (Elaeis guineensis Jacq.): EFEKTIVITAS ZPT ALAMI EKSTRAK TOGE DAN NPK 15-15-6-4 TERHADAP PERTUMBUHAN BIBIT KELAPASAWIT (Elaeis guineensis Jacq.) - Dewi Yana; Mulyanti; Muzakir; Saprizal (ROCE : Jurnal Pertanian Terapan, 2026)
Nursery management is a process of growing and developing seeds into seedlings ready for planting. This study aimed to determine the effectiveness of a natural plant growth regulator (bean sprout extract) and NPK 15-15-6-4 fertilizer on the growth of oil palm (Elaeis guineensis Jacq.) seedlings and to provide a recommended dosage for pre-nursery oil palm seedling growth. This study employed a non-factorial Randomized Complete Block Design (RCBD) with five treatments and five replications, resulting in 25 experimental units. The treatments were arranged as follows: K0 = Without bean sprout extract and NPK 15-15-6-4 (control); K1 = 10 ml bean sprout extract per seedling + 30 g NPK 15-15-6-4; K2 = 20 ml bean sprout extract per seedling + 30 g NPK 15-15-6-4; K3 = 30 ml bean sprout extract per seedling + 30 g NPK 15-15-6-4; K4 = 40 ml bean sprout extract per seedling + 30 g NPK 15-15-6-4. The observed parameters were plant height, leaf number, and stem diameter. The results showed that the application of bean sprout extract as a plant growth regulator and NPK 15-15-6-4 fertilizer did not significantly affect plant height, leaf number, or stem diameter of oil palm seedlings at 40–60 days after planting. The best treatment was K4 (40 ml of bean sprout extract and 30 g of NPK 15-15-6-4), which improved oil palm seedling growth.